2007
DOI: 10.1111/j.1464-410x.2007.07110.x
|View full text |Cite
|
Sign up to set email alerts
|

The associations among eNOS G894T gene polymorphism, erectile dysfunction and related risk factors

Abstract: OBJECTIVE To investigate the possible correlations among eNOS G894T polymorphism, erectile dysfunction (ED) and related risk factors in a Taiwanese population. MATERIALS AND METHODS In all, 151 patients with ED and 77 healthy controls were enrolled. All the men had a complete clinical history taken and laboratory data was collected. To assess erectile conditions the five‐item version of the International Index of Erectile Function (IIEF‐5) was used. The eNOS G894T polymorphisms were determined using the polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
(36 reference statements)
1
23
0
1
Order By: Relevance
“…According to the previous reports, we were able to rule out that the risk for ED and the response to prostaglandin E1 is associated with the genotype in the eNOS G894T polymorphism. Up to now, only a study from a Mexican mestizan population with 56 patients and a study of 156 ED patients in Taiwan were able to show an association between the eNOS G894T genotype and the risk for ED (Rosas-Vargas et al, 2004;Lee et al, 2007). Taking into account that the number of individuals investigated in both studies is rather small and that even in the well designed study in Taiwan the observed association between the eNOS G894T polymorphism the t-allele frequency was 80.0% in the ED group and 63.3% in the control group (P = 0.04), further studies with larger study cohorts are necessary to assess the effect of the eNOS G894T genotype on the risk for ED.…”
Section: Discussionmentioning
confidence: 97%
“…According to the previous reports, we were able to rule out that the risk for ED and the response to prostaglandin E1 is associated with the genotype in the eNOS G894T polymorphism. Up to now, only a study from a Mexican mestizan population with 56 patients and a study of 156 ED patients in Taiwan were able to show an association between the eNOS G894T genotype and the risk for ED (Rosas-Vargas et al, 2004;Lee et al, 2007). Taking into account that the number of individuals investigated in both studies is rather small and that even in the well designed study in Taiwan the observed association between the eNOS G894T polymorphism the t-allele frequency was 80.0% in the ED group and 63.3% in the control group (P = 0.04), further studies with larger study cohorts are necessary to assess the effect of the eNOS G894T genotype on the risk for ED.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, HHCy is a recognized risk factor for endothelial dysfunction and related disorders, including CVD and ED2021. NO, the key mediator synthesized by different NO synthase isoenzymes (eNOS, nNOS, and inducible NOS), plays an essential role in endothelial function222324. Sexual stimuli induce an increase in serum levels of testosterone and the release of NO from penile nerve endings and endothelial cells, which in turn relax cavernous smooth muscle and increase blood flow to the penis25.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported in recent years that 27 bp-VNTR polymorphism in eNOS gene locus is related with many kinds of clinic diseases, such as primary hypertension, type 2 diabetes mellitus, cerebral infarction, coronary heart disease, asthma, and other ischemic cardiovascular and cerebrovascular diseases (Benjafield and Morris, 2000;Hoffmann et al, 2005;Matyar et al, 2005;Mearin et al, 2006;Uthra et al, 2007). G894T polymorphism in exon 7 of eNOS gene as a missense mutation, affects eNOS protein and is related with the spasm of coronary arteries, myocardial infarction, primary hypertension, left ventricular hypertrophy, artherosclerosis, erectile dysfunction, and cerebral infarction (Li et al, 2005;Tang et al, 2008;Lee et al, 2007;Antoniades et al, 2007;Reali et al, 2008). Recently, an eNOS polymorphism, Glu298Asp, is implicated in osteoporosis.…”
Section: Introductionmentioning
confidence: 99%